2009
DOI: 10.1158/1541-7786.mcr-08-0056
|View full text |Cite
|
Sign up to set email alerts
|

p31comet Induces Cellular Senescence through p21 Accumulation and Mad2 Disruption

Abstract: Functional suppression of spindle checkpoint protein activity results in apoptotic cell death arising from mitotic failure, including defective spindle formation, chromosome missegregation, and premature mitotic exit. The recently identified p31 comet protein acts as a spindle checkpoint silencer via communication with the transient Mad2 complex. In the present study, we found that p31 comet overexpression led to two distinct phenotypic changes, cellular apoptosis and senescence. Because of a paucity of direct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
(56 reference statements)
4
22
0
2
Order By: Relevance
“…These results are consistent with a recent paper showing that p53 depletion permits the accumulation of non-diploid cells, suggesting involvement of p53 in a ''tolerance'' mechanism of aneuploid cells (Thompson and Compton, 2010). Another recent article evidenced a link between Mad2 and p21 WAF1 , in particular Mad2 reduction was associated to p21 WAF1 increase following over-expression of p31 comet , a Mad2 interacting protein, considered a ''silencer'' of the SAC (Yun et al, 2009). Moreover, it was shown that Mad2 overexpression is associated with aneuploidy induced by inactivation of pRb and p53tumor suppressors in tumor cells (Schvartzman et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with a recent paper showing that p53 depletion permits the accumulation of non-diploid cells, suggesting involvement of p53 in a ''tolerance'' mechanism of aneuploid cells (Thompson and Compton, 2010). Another recent article evidenced a link between Mad2 and p21 WAF1 , in particular Mad2 reduction was associated to p21 WAF1 increase following over-expression of p31 comet , a Mad2 interacting protein, considered a ''silencer'' of the SAC (Yun et al, 2009). Moreover, it was shown that Mad2 overexpression is associated with aneuploidy induced by inactivation of pRb and p53tumor suppressors in tumor cells (Schvartzman et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The siRNA oligonucleotides were chemically synthesized at Dharmacon RNA Technologies (Lafayette, CO, USA). The sequences for siRNAs used in this study were human Mad2 (5 0 -AAGTGGTGAGGTCCTGGAAAG-3 0 ), 35 human BubR1 (5 0 -AACGGGCAUUUGAAUAUGAAA-3 0 ), 36 human Mad1 (5 0 -AACAGGCA GTGTCAGCAGAAC-3 0 ), 37 and human MTBP#1 (5 0 -GCCACAUUGAUUCACU CAGUU-3 0 ). Human MTBP#2 and control non-target 1 siRNAs were purchased from Santa Cruz Biotechnology and Dharmacon RNA Technologies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These include, but are not limited to, the activation of the DNA damage-responsive protease caspase-2, 114 of the tumor suppressor TP53 109,115 and of other members of the TP53 family, including the TP73 variant TAp73. 116,117 In view of recent results from several laboratories indicating that mitotic aberrations can induce cell senescence, [118][119][120] and that cell death can be either apoptotic or necrotic, 8 we have recently proposed a novel definition and categorization of mitotic catastrophe based on purely functional considerations. 108 Thus, mitotic catastrophe would not constitute a 'pure' cell death executioner pathway, but an oncosuppressive mechanism that: (i) is initiated by perturbations of the mitotic apparatus (i.e., chromosomes and the complex Figure 3 Regulated necrosis.…”
Section: Definition Of 'Mitotic Catastrophe'mentioning
confidence: 99%